Implementation of the Zakat Policy as One of the Efforts to Reduce Poverty in Indonesia - Didin Muhafidin (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The fight against poverty is an ongoing task for emerging nations like Indonesia, which is one of those nations. The number of people living in poverty in Indonesia is increasing, despite the fact that several government programs aimed at alleviating poverty have been introduced; these programs do not appear to be trustworthy enough to solve the problems they were intended to solve. The purpose of this study is to investigate how the policy of zakat has been implemented in Indonesia in an effort to lessen the country's level of poverty. This research makes use of a qualitative descriptive approach by looking at research from libraries. According to the findings, the potential for zakat in Indonesia has reached an astounding quantity, which indicates that zakat may be utilized as an alternate method for addressing the issue of poverty in Indonesia. It is reasonable for the people of Indonesia to have hope that the country's poverty rate will begin to decline as soon as professional management is implemented. According to the findings of this study, maximizing the potential of zakat would bring economic prosperity to the community. This is something that will certainly be promoted by the participation of all aspects of the nation.